Interventions to Enhance English Teachers’ Participation in the Scholarship of Teaching and Learning: Kalahari Circuit English as a Second Language Teachers’ Voices - Josua, Lukas Matati; Iitula, Leena Kaunapawa; Hamakali , Hafeni Pamwenase Shikalepo; Amakali, Justina Latenda (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2024)
The paucity of English teachers in Namibia’s research output as well as practicing the scholarship of teaching and learning has been noticed and noted. Therefore, the purpose of this study is to evaluate the views of English teachers in the Kalahari Circuit in the ||Kharas Region in Namibia on the effect of an intervention to enhance their willingness to conduct research and publish. The study used a questionnaire to collect qualitative and quantitative biographical data from the participants. The quantitative data were analysed using simple description while qualitative data were analysed using Renner and Tylor-Powell’s five steps for analysing narratives. The study revealed that, after participating in the research workshop, English teachers showed confidence to conduct research and publish their work. Furthermore, the participants suggested that the workshop should include all teachers, who need support from the agents in education. It was also found that the duration of the workshop should be extended and resources should be availed to teachers to conduct research for publication. The study recommended that this training should be rolled out to other regions while broadening the target scope.